STRATEGI AUDIT JARAK JAUH DIMASA PANDEMI (Remote Audit Strategy During Pandemic) - Istiqomah, Rahayu (JURNAL EKONOMIKA, 2023)
Penelitian ini bertujuan untuk memberikan prosedur alternatif atau strategi audit bagi auditor eksternal pemerintah maupun non pemerintah selama pandemi covid serta pemanfaatan teknologi informasi untuk tetap dapat memberikan hasil audit berkualitas. Metode dalam penelitian ini deskriptif kualitatif melalui kajian literatur. Berbagai prosedur alternatif yang dapat diterapkan selama masa pandemi diantaranya pemanfaatan teknologi seperti video/video conference untuk cash opname, stock opname, inspeksi belanja barang/jasa dan modal, foto-foto pekerjaan dilengkapi geotagging, surat elektronik/email untuk konfirmasi dan permintaan keterangan, dan salinan digital dokumen pengujian. Teknologi informasi yang dapat membantu pelaksanaan audit di masa pandemi antara lain teknik audit berbantuan komputer, big data analytics, dan artificial intelligence.ABSTRACTThis study aims to provide an alternative procedures or audit strategies for government and non-government external auditors during the covid pandemic as well as the use of information technology to continue to provide quality audit results. The method in this research is descriptive qualitative through a literature review. Various alternative procedures that can be applied during the pandemic include the use of technology such as video/video conferencing for cash opname, stock taking, an inspection of goods/services and capital expenditures, photos of work equipped with geotagging, electronic mail/email for confirmation and inquiries, and digital copy of the text document. Information technology that can help carry out audits during a pandemic includes computer-assisted audit techniques, big data analytics, and artificial intelligence.